DINAMIKA PROSES PEMEKARAN KECAMATAN PULAU MERBAU KABUPATEN KEPULAUAN MERANTI - Heru Kurniawan; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
After the implementation of regional autonomy and based on the laws of the local government, all central government employees who previously worked as a clerk in the center of the area assigned to each local government. One of the areas in the extract is a division of districts where the granting authority for a county / city to expand the sub-district / increase the number of sub-districts through the provision at the local level of government affairs under the authority of the village. One of the sub-districts of meranti, namely sub-district consists of two islands merbau namely desert islands and islets merbau. Merbau islands separated by desert island so difficult range of transport links and good communication pemerntahan affairs and public affairs. If seen the formation of sub-district in 2011 merbau island has been through the dynamics of the process so long as the proposed establishment of this district has been started since 2002, so long his view of the authors was interested in doing this research in the future because of the formation process is so long that for 9 years . When viewed from various aspects of the island has long merbau eligible for expandedKey words : Decentralization and Regional Autonomy, pemekeran for